2008
DOI: 10.1210/en.2008-0293
|View full text |Cite
|
Sign up to set email alerts
|

Orexin-A Hyperphagia: Hindbrain Participation in Consummatory Feeding Responses

Abstract: Orexin-A (ORXA) is an orexigenic neuropeptide produced by the lateral hypothalamus that increases food intake when injected into the brain ventricles or forebrain nuclei. We used a licking microstructure analysis to evaluate hindbrain and forebrain ORXA effects in intact and hindbrain-lesioned rats, to identify the motivational and anatomical bases of ORXA hyperphagia. Intact rats with cannulas in the fourth brain ventricle (4V) received vehicle (artificial cerebrospinal fluid) or ORXA (0.1, 0.4, 1, or 10 nm) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 70 publications
6
56
0
Order By: Relevance
“…Furthermore, local application of orexin in the PVH, DMH, and LHA was shown to increase food intake 45,46 . A recent study showed that the area postrema and NTS are involved in the orexin mediated feeding 47 . Application of orexin A into the nucleus of accumbens shell was reported to increase feeding 48 .…”
Section: -1 Orexin and Feeding Behaviormentioning
confidence: 99%
“…Furthermore, local application of orexin in the PVH, DMH, and LHA was shown to increase food intake 45,46 . A recent study showed that the area postrema and NTS are involved in the orexin mediated feeding 47 . Application of orexin A into the nucleus of accumbens shell was reported to increase feeding 48 .…”
Section: -1 Orexin and Feeding Behaviormentioning
confidence: 99%
“…The 0.1 M and 1 M sucrose solutions often produce distinct licking microstructure profiles, even though these differences can result in the same volume consumed (4,5,9). We have shown that rats exhibit robust licking responses for 1 M sucrose, as indicated by a rapid initial rate of licking, larger mean lick burst sizes/durations (reflecting taste evaluation), and a steep rate of decline in the ingestion rate due to the caloric load, which generates a meal of moderate duration (2). When offered the less caloric and less preferred 0.1 M sucrose solution, rats exhibit slower initial lick rates and smaller and shorter licking bursts (suggesting weaker ingestive taste reactivity), and a flatter rate of decline in ingestion rate, with a longer meal duration and more bursts of licking, reflecting the reduced caloric inhibition (see also Refs.…”
Section: Methodsmentioning
confidence: 87%
“…3,51 Additionally, the area postrema and nucleus of tractus solitarius have effects on meal size, but not on meal frequency. 3 The area postrema and the nucleus of tractus solitarius both promote orexin-mediated feeding behaviors, suggesting that they represent a robust link to the feeding centers in the LHA.…”
Section: Area Postrema and Nucleus Of Tractus Solitariusmentioning
confidence: 99%
“…3,51 Additionally, the area postrema and nucleus of tractus solitarius have effects on meal size, but not on meal frequency. 3 The area postrema and the nucleus of tractus solitarius both promote orexin-mediated feeding behaviors, suggesting that they represent a robust link to the feeding centers in the LHA. The nucleus of tractus solitarius is the primary satiety relay center to the CNS from the gastrointestinal tract via N-methyl-d-aspartic acid (NMDA) receptor-mediated activation by vagal afferents, 9,13,36,94 making DBS of this region an attractive proposition.…”
Section: Area Postrema and Nucleus Of Tractus Solitariusmentioning
confidence: 99%